CEO pulchronomics and appearance discrimination. Issue 3 (10th August 2021) - Kim, Jung Yeun (June); Shi, Linna; Zhou, Nan
Abstract : Purpose: Pulchronomics studies the economics of beauty. The purpose of this paper is to research CEO pulchronomics by examining whether a beauty premium exists in CEO compensation and whether this beauty premium is justified by differences in CEO performance. Design/methodology/approach: The authors calculate a facial attractiveness scores (FAS) based on facial symmetry, facial structure and the golden ratio. The authors then perform OLS regressions to examine the effect of CEO beauty on CEO compensation and firm performances. Findings: The authors find that base salaries for attractive CEOs are higher than those for unattractive CEOs, but incentive pays for attractive CEOs are not different from those for unattractive CEOs. The latter is likely due to the fact that attractive CEOs do not outperform unattractive CEOs in operations, innovation, corporate social responsibility and financial reporting quality. Originality/value: Since the CEO beauty premium is not supported by the superior performance of attractive CEOs, this paper provides new evidence of appearance discrimination in CEO compensation.